Fall prevention modulates decisional saccadic behavior in aging - Coubard, Olivier A. (Frontiers in Aging Neuroscience, 2012)
As society ages and frequency of falls increases in older adults, counteracting motor decline is a challenging issue for developed countries. Physical activity based on aerobic and strength training as well as motor activity based on skill learning both help benefit balance and reduce the risk of falls, as assessed by clinical or laboratory measures. However, how such programs influence motor control is a neglected issue. This study examined the effects of fall prevention (FP) training on saccadic control in older adults. Saccades were recorded in twelve participants aged 64-91 years before and after 2.5-month training in FP. Traditional analysis of saccade timing and dynamics was performed together with a quantitative analysis using the LATER model, enabling us to examine the underlying motor control processes. Results indicated that FP reduced the rate of anticipatory and express saccades in inappropriate directions and enhanced that of express saccades in the appropriate direction, resulting in decreased latency and higher left-right symmetry of motor responses. FP reduced within-participant variability of saccade duration, amplitude, and peak velocity. LATER analysis suggested that FP modulates decisional thresholds, extending our knowledge of motor training influence on central motor control. We introduce the TIMER-RIDER model to account for the results.